Reflections of Czechs in German Racial Science and Nazi Racial Ideology (Theatrum historiae, 2013)
The racial issues were a major part of the Nazi ideology and policy. It was not only the racial anti-Semitism, but also the theory of supremacy of the Nordic race. According some racial theorists, the major part of the Slavs was to be racially inferior due to the predominance of the East-Baltic, Alpine and even Mongoloid races. Their opinions on the Czechs changed during the time. The aim of the article is to show how the Nazi racial experts looked at the Czech nation and whether the results of their surveys confirmed or refuted their assumptions.
Keywords: Nazi racism; anti-Slavism; racial surveys; Czechs; Germanization; racial policy; Protectorate of Bohemia and Moravia